Determined spirits : eugenics, heredity and racial regeneration in Anglo-American spiritualist writing, 1848-1930 /: eugenics, heredity and racial regeneration in Anglo-American spiritualist writing, 1848-1930. ([2012]) - Ferguson, Christine
No abstract available